Frontispiece: Sky‐Blue Triplet Emitters with Cyclometalated Imidazopyrazine‐Based NHC‐Ligands and Aromatic Bulky Acetylacetonates. Issue 64 (18th November 2019) - Pinter, Piermaria; Soellner, Johannes; Strassner, Thomas
Abstract : Platinum(II) complexes with a cyclometalated NHC ligand (C^C*) are very efficient blue triplet emitters for OLED applications. In their Communication on page 14495 ff., Strassner et al. describe the use of C^C* ligands based on the imidazopyrazine motif together with a bulky acetylacetonate co‐ligand to provide platinum(II) complexes with exceptional phosphorescent properties, such as high quantum yields and among the shortest decay times observed for this class of complexes.